An Innovative Foundation Technology For The Construction Of Retaining Walls In Urban Areas - Introduction - F. Pagliacci (Deep Foundations Institute, 2000)
Retaining walls for the construction of underground urban infrastructures have to be executed considering the impact of a deep foundation job-site within an urban network. Traditional excavation systems, based on the use of grabs and bentonite mud, involve serious problems such as: the opening of trenches adjacent to existing buildings; the cleaning of the working area; the site installation for the production and storage of the bentonite mud; the transport and disposal of soil contaminated with bentonite mud. Alternative solutions have therefore been developed in order to overcome these problems. For temporary works soil consolidation methods, combined with the use of sheet piles, have been implemented, by a combination of traditional mixing methods and jet grouting systems to speed up the operations, consequently reducing the construction time. For permanent works two new techniques named respectively CSP (Cased Secant Piles) and CDW (Continuous Diaphragm Walls) have been studied, applied and tested.